The effects of different levels of brush end rounding on gingival abrasion: a double‐blind randomized clinical trial. Issue 4 (3rd March 2016) - Hennequin‐Hoenderdos, NL; Slot, DE; Van der Sluijs, E; Adam, R; Grender, JM; Van der Weijden, GA
Abstract: Objective: The objective of this study was to evaluate the effect of different levels of filament end rounding on gingival abrasions (GAs). Methods: The study was a crossover, split‐mouth, contra‐lateral, double‐blinded, randomized design using professional brushing. Three manual toothbrushes, with 0%, 40–50% and >90% end‐rounded filaments, were investigated. Participants refrained from all oral hygiene procedures for 48 h prior to each of the three visits. Prior to brushing, oral soft tissue (OST) and GAs were assessed. Based on the randomization, during every visit contra‐lateral quadrants were brushed with one of the three test brushes. After brushing, GAs were re‐assessed. The means of the GAs prebrushing and post‐brushing and differences per brush were calculated. Subanalyses were performed based on the size of the abrasion and its location. Results: A total of 46 generally healthy participants without periodontitis completed the study and provided a full data set. All brushes had statistically significant increases of abrasions following their use ( P < 0.001). Non‐end‐rounded brushes provided significantly more GAs than did the 40–50% and the >90% brushes ( P ≥ 0.001). A subanalysis showed that significantly more small‐sized ( P ≥ 0.002) abrasions located at the gingival margin ( P < 0.001) occurred when a non‐end‐rounded brush was used. No significant differences were found between the 40–50% and >90% end‐rounded brushes in any of the analyses. OST deviations were not observed. Conclusions: Based on the results of this experiment involving professional brushing, it can be concluded that 40–50% or greater end‐rounded filaments can provide a significant reduction in gingival abrasions compared to non‐end‐rounded filaments.